New dimensions of bleisure tourism – Synergies between business and leisure travel in the context of sustainable development in Hungary - Boros, Kitti; Csordás, Tamás; Markos-Kujbus, Éva (Marketing & Menedzsment, 2025)
THE AIMS OF THE PAPER Bleisure tourism, defined as the combination of business and leisure travel, is becoming an increasingly significant phenomenon within business tourism. This research explores the sustainability considerations identified through a comparative analysis of business and bleisure tourism, with particular emphasis on the role of service providers in Hungary. This study’s theoretical framework is positioned at the intersection of business tourism, bleisure tourism, and sustainability and is informed by established theories on consumer decision-making, adaptive mechanisms in tourism service provision, and sustainable development. METHODOLOGY In the preliminary phase of the study, interviews with 41 conference participants were conducted. This was followed by 46 interviews conducted with senior representatives of Hungarian hotels, event venues, as well as companies specialising in business event planning, and corporate travel management. The interviews were carried out in the first quarter of 2025. MOST IMPORTANT RESULTS The findings of these interviews indicate that while service providers have encountered the phenomenon of bleisure tourism, its conceptual definition remains relatively unfamiliar to them. Results show that bleisure tourism manifests across multiple dimensions, including variations in the duration of extended stays, preferences for specific leisure activities, and the customisation of package offerings by service providers. The findings highlight a dual-faceted impact on sustainability: while extending the duration of business trips may reduce travel frequency and its associated environmental footprint, sustainability strategies among service providers remain in an early stage of development, with only a low potential to reduce emissions and promote local culture. RECOMMENDATIONS This research contributes to tourism studies by examining the sustainability dimensions of bleisure travel, highlighting the potential for aligning business–leisure patterns with environmental objectives. It also offers practical guidance for supply-side actors to develop sustainable business models and tailored packages that integrate bleisure principles.